EFFECT OF DIFFERENT PLANT SPECIES ON TILAPIA (OREOCHROMIS SP.) GILL HISTOPATHOLOGY AND WATER QUALITY IN AQUAPONICS SYSTEMS - Pandiangan I.A.H. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Currently, tilapia farming focuses on efficient use of water in reducing nitrogen waste by implementing aquaponics systems. The application of an aquaponic system has advantages not only for producing fish but also plants.This research was carried out for 1 month with different types of plants used, namely water spinach (Ipomoea reptans), pakcoy (Brassica rapa L), and control. Each treatment was repeated 3 times. Tilapia fish were used in this study ranging at 8-10 cm in an aquarium (60x40x30 cm) with a stocking density of 1 fish/2 liters. Parameters observed included gill histopathology and water quality (ammonia, nitrite and nitrate). The results showed that the damage of fish gill found in the form of hyperflasia, fusion and hemorrhage. The lowest damage to fish gill tissue occurred in treatment A (water spinach) with a score of hyperplasia (0.73), fusion (0.07) and hemorrhage (1.33). The best water quality was obtained in treatment A (water spinach) with values of ammonia (0.25 mg/l), nitrite (0.174 mg/l), and nitrate (1.058 mg/l).There is a correlation between the amount of damage to the fish gills and the quality of the water in the rearing media in which the higher the concentration of ammonia and nitrite, the greater the level of damage obtained. Thus, water spinach is the effective plant to utilize nitrogen as an essential nutrient for growth in the aquaculture system.